Unravelling the gut-brain connection: a systematic review of migraine and the gut microbiome - Caroline W Mugo; Ella Church; Richard D Horniblow; Susan P Mollan; Hannah Botfield; Lisa J Hill; Alexandra J Sinclair; Olivia Grech (The Journal of Headache and Pain)
Abstract Background There is substantial evidence linking migraines to gastrointestinal (GI) issues. Conditions such as irritable bowel syndrome and colitis often co-occur with migraines and GI symptoms are common among migraine patients. However, the evidence supporting the efficacy of gut microbiome-targeted therapies for managing migraines is limited. This systematic review aimed to describe the existing evidence of the gut microbiome in patients with migraine compared to healthy individuals. Additionally, it sought to examine how therapies targeting the gut microbiome including prebiotics, probiotics and synbiotics, might influence clinical outcomes. Methods We performed searches on Embase, PubMed, and the Cochrane Library to identify studies in migraines and the gut microbiome, focusing on those which investigated the gut microbiome composition and gut microbiome-targeted therapies. Key data was extracted and analysed including study details, patient demographics, migraine type, comorbidities, and clinical outcomes. For gut microbiome composition studies, bacterial diversity and abundance was noted. For gut microbiome-targeted therapies studies, treatment types, dosages, and patient outcomes was recorded. Results A significant difference between various genera of microbes was reported between migraine patients and controls in several studies. Bacteroidetes (also named Bacteroidota), proteobacteria, and firmicutes (also named Bacillota) phyla groups were found significantly abundant in migraine, while studies were conflicted in the abundance of Actinobacteria and Clostridia with regards to increased migraine risk in migraine patients. Patients with migraine had a gut microbiome with reduced species number and relative abundance, as well as a distinct bacterial composition compared to controls. Synbiotic and synbiotic/probiotic combination treatments have been shown in five randomised controlled trials and one open label pilot study to significantly decrease migraine severity, frequency, duration and painkiller consumption. Conclusions The significant alterations in microbial phyla observed in migraine patients suggest a potential microbial signature that may be associated with migraine risk or chronic progression. However, the mechanistic underpinnings of these associations remain unclear. This systemic review found that probiotic and synbiotic/probiotic combination therapies may be promising interventions for migraine management, offering significant reductions in migraine frequency and painkiller use. Future randomised controlled studies are needed to evaluate the optimal length of treatment and impact on patient related quality of life.